Effect of post-match cold-water immersion on subsequent match running performance in junior soccer players during tournament play - Rowsell, G. J.; Coutts, A. J.; Reaburn, P.; Hill-Haas, S. (Journal of Sports Sciences, 2011)
In this study, we investigated the effects of two hydrotherapy interventions on match running performance and perceptual measures of fatigue and recovery during a 4-day soccer tournament. Twenty male junior soccer players were assigned to one of two treatment groups and undertook either cold-water immersion (5 × 1 min at 10°C) or thermoneutral water immersion (5 × 1 min at 34°C) after each match. High-intensity running distance (>15 km/h) and total distance covered, time spent in low (<80% maximum heart rate), moderate (80-90% maximum heart rate), and high (>90% maximum heart rate) heart rate zones, and rating of perceived exertion (RPE) were recorded for each match. Perceptions of general fatigue and leg soreness were recorded approximately 22 h after each match. There were decreases in both groups across the 4-day tournament for high-intensity running distance (P = 0.006, Cohen's d = 0.63), total distance run (P < 0.001, d = 0.90), time in high heart rate zone (P = 0.003, d = 0.90), and match RPE (P = 0.012, d = 0.52). Cold-water immersion was more effective than thermoneutral immersion for reducing the perception of leg soreness (P = 0.004, d = -0.92) and general fatigue (P = 0.007, d = -0.91), ameliorating the decrement in total distance run (P = 0.001, d = 0.55), and maintaining time in the moderate heart rate zone (P = 0.01, d = 1.06). In conclusion, cold-water immersion mediates the perceptions of fatigue and recovery and enhances the restoration of some match-related performance measures during a 4-day tournament.